Impact of Total Quality Management Toward Education Quality at Vocational School - Venny Wismayanti; Isjoni Isjoni; Azhar Azhar (AL-ISHLAH: Jurnal Pendidikan, 2025)
In response to global challenges, education systems must develop high-quality human resources capable of competing internationally. Total Quality Management (TQM) is proposed as a strategic approach to improve educational outcomes, particularly in Vocational High Schools (SMK). This qualitative study employed a case study method involving three informants: a school principal, a teacher, and an administrative staff member. Data were gathered through interviews, observations, and document analysis. The data were analyzed using data reduction, data presentation, and conclusion-drawing techniques. The findings indicate that TQM implementation contributes to enhancing education quality in vocational schools. The evaluation focused on three key indicators: leadership management, teacher performance, and school administration. Leadership and teacher management were found to be well-executed, particularly in teaching and learning activities. However, administrative functions were only categorized as adequate, highlighting the need for improvement in this area. The application of TQM demonstrates positive impacts on school management and instructional practices. While leadership and teaching practices align with quality standards, administrative processes require further development to support comprehensive school improvement. TQM can effectively enhance educational quality in vocational high schools, but successful implementation depends on strengthening administrative management alongside instructional and leadership practices.